Characterization of the human properdin gene. - Nolan, K; Kaluz, S; Higgins, J; Goundis, D; Reid, K (1992)
A cosmid clone containing the complete coding sequence of the human properdin gene has been characterized. The gene is located at one end of the approximately 40 kb cosmid insert and approximately 8.2 kb of the sequence data have been obtained from this region. Two discrepancies with the published cDNA sequence [Nolan, Schwaeble, Kaluz, Dierich and Reid (1991) Eur. J. Immunol. 21, 771-776] have been resolved. Properdin has previously been described as a modular protein, with the majority of its sequence composed of six tandem repeats of a sequence motif of approximately 60 amino acids which is related to the type-I repeat sequence (TSR), initially described in thrombospondin [Lawler and Hynes (1986) J. Cell Biol. 103, 1635-1648; Goundis and Reid (1988), Nature (London) 335, 82-85]. Analysis of the genomic sequence data indicates that the human properdin gene is organized into ten exons which span approximately 6 kb of the genome. TSRs 2-5 are coded for by discrete, symmetrical exons (phase 1-1), which supports the hypothesis that modular proteins evolved by a process involving exon shuffling. TSR1 is also coded for by a discrete exon, but the boundaries are asymmetrical (phase 2-1). The sequence coding for the sixth TSR is split across the final two exons of the gene with the first 38 amino acids of the repeat coded for by an asymmetric exon (phase 1-2). This split at the genomic level has been shown, by alignment analysis, to be reflected at the protein level with the division of repeat 6 into TSR-like and TSR-unlike sequences.